Bargain or bust? Prices, discounts, and returns in the market for real estate foreclosures - Alexander Daminger; Simon Wiersma (Austrian Institute of Economic Research (WIFO), 2024)
We examine foreclosure discounts and their subsequent impact on investor returns in Berlin's housing market from 1984 to 2022. Utilizing hedonic regression models and matching techniques on a data set of housing transactions, we determine that foreclosure discounts, ranging from 20% to 50%, are significant and persist over time. In a repeat sales approach, in which we explicitly account for the sequence of transactions, we show that initial investments in foreclosed properties yield average annualized returns surpassing matched non-distressed counterparts by 20.5 percentage points. However, when a foreclosure follows a regular sale, the average annualized returns are 9.6 percentage points lower than in matched non-distressed transaction pairs. Novel to the literature, we further show that this markdown is only associated with the foreclosure transaction, rather than putting a permanent stigma on the foreclosed apartment. Our ability to control for both observed and unobserved property characteristics suggests that this discount may be attributed to both a foreclosure stigma and the format used for foreclosure auctions in Germany. Consequently, our paper not only advances the foreclosure literature with new insights from a global city but also contributes to the discourse on auctions in a real estate context.
Keywords: R31; G12; D44; 330; Foreclosure Discounts; Real Estate Investments; Housing Market Dynamics